New tectono-geochronological constraints on timing of shearing along the Ailao Shan-Red River shear zone: Implications for genesis of Ailao Shan gold mineralization - Liu, Junlai; Chen, Xiaoyu; Wu, Wenbin; Tang, Yuan; Tran, My-Dung; Nguyen, Quang-Luat; Zhang, Zhaochong; Zhao, Zhidan (Journal of Asian earth sciences, 2015)
[Display omitted] •The Ailao Shan belt consists of three units including the ASRR shear zone and the Ailao Shan suture zone, etc.•New dating results constrain the ductile shearing along the ASRR shear zone in ca. 30–22Ma.•The Ailao Shan gold formed due to post-collisional extension prior to the shearing. Several world class gold deposits are located along the Ailao Shan (ALS) belt in eastern Tibet, China. The genesis of gold mineralization along the belt, however, has been the subject of debates in the last decades, which highlights the importance of dating shearing, magmatism and mineralization along the Ailao Shan-Red River shear zone (ASRR). Through detailed field observations and microscopic analysis, a group of leucocratic intrusions from within and outside the shear zone along the ALS belt are investigated in the present paper. Pre-, syn- and post-shearing intrusions are grouped based on structural and microstructural analysis. LA-ICP-MS and SIMS dating of the intrusions revealed the existence of two age populations, a group of ages older than 30Ma and the other younger than 28Ma. The former are distributed both within and outside the shear zone, and the latter, in contrast, occur only within the shear zone. Our new results show that the ductile shearing along the ASRR shear zone initiated since ca. 30Ma ago. The dating results place major constraints on timing of shearing along the ASRR shear zone and have profound implications on the genesis of gold mineralization along the ALS belt. The present study reveals that ductile shearing along the ASRR shear zone was resulted from extrusion of the Indochina block late during the Indian–Eurasian plate collision. Meanwhile, we conclude that the gold mineralization took place prior to the shearing, but in close relation to an early magmatism (>30Ma) ascribed to post-collisional extension collapse involving mantle processes, early during the plate collision.